(untitled) (International journal of artificial intelligence, 2025)
This article comprehensively discusses the theoretical and practical foundations of the competency-based approach in developing technical thinking during economics lessons. The competency-based approach emphasizes not only the acquisition of knowledge but also its integration with skills and abilities, enabling students to apply them in practice, conduct independent research, and solve real-life problems effectively. Technical thinking refers to the ability to analyze economic processes logically, model them using mathematical methods, and develop optimal solutions through innovative approaches. The article examines the theoretical basis of technical thinking, the methods used in teaching economic sciences, the advantages of a competency-based approach, and the role of digital educational resources. Furthermore, it highlights advanced practices and methodological recommendations for fostering students’ professional competencies within the educational process.